2022
DOI: 10.3390/coatings13010015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Surface Stereometry of Alloyed Austenitic Steel after Fibre Laser Cutting using Confocal Microscopy

Abstract: The paper extends the concept of cut edge quality and examines the fibre laser cutting process. A Prima Power Platino Fiber Evo device with a reference speed (RS) of 3500 mm/min was used for laser cutting. In order to analyse the influence of the laser cutting speed on the cut edge quality of X5CrNi18-10 stainless steel sheets, macroscopic studies were conducted on a stereoscopic microscope and surface stereometry on a confocal microscope. The obtained results were analysed to evaluate 2D and 3D parameters. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…Although carbon steel is the most widely used in the petrochemical industry, other base materials must be addressed. For example, stainless steel [51] can be better resistant to corrosion and high pressure, and relatively require error-free. Otherwise, the consequences will be rather severe.…”
Section: Discussionmentioning
confidence: 99%
“…Although carbon steel is the most widely used in the petrochemical industry, other base materials must be addressed. For example, stainless steel [51] can be better resistant to corrosion and high pressure, and relatively require error-free. Otherwise, the consequences will be rather severe.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [20] found that laser cutting also had an effect on the magnetic properties of the edge, which was manifested as a decrease in the relative magnetic permeability of the overall sample. Krajewski et al [21] observed the cut edge after laser cutting with confocal microscopy and confirmed that the laser cutting speed had a significant impact on the cut-edge quality. Chang et al [22] analyzed the effects of mechanical shearing, laser cutting, and WEDM on the straight-edge cutting performance of medium-Mn steel.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, the quality of the cutting edges is also crucial during the final technological operations, such as powder-coating or galvanizing. The adhesion of the coating is directly dependent on the quality of the cutting edges, as evidenced by research studies [11,12]. Solving such laser-cutting quality problems is particularly important because the insufficient quality of manufactured parts can affect their durability and reliability [13].…”
Section: Introductionmentioning
confidence: 99%